2016
DOI: 10.1007/s11104-016-2993-z
|View full text |Cite
|
Sign up to set email alerts
|

Plant species, temperature, and bedrock affect net methane flux out of grassland and forest soils

Abstract: Aims The objectives of this study were to investigate the influence of plants on net methane flux from forest and grassland soils depending on bedrock, temperature, and plant species, and to determine the abundance of methanogenic and methanotrophic microorganisms. Methods Lab-scale gas measurements with forest and grassland soils and different site-specific plants were performed. Next-generation sequencing was conducted to characterize the archaeal community structure and the abundance of methanotrophic bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 62 publications
2
26
0
1
Order By: Relevance
“…The results also show some variation in both the belowground CH4 fluxes and the amount of methanotrophs between the species, V. vitis-idaea-rooted-soils indicating the strongest uptake. The effect of plant species and vegetation types on soil CH4 fluxes has also been shown by other studies (Praeg et al 2016;Maier et al 2017b). These differences can result from the different plant species effects on soil microbes, which may again result from the root exudates (Innes et al 2004).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results also show some variation in both the belowground CH4 fluxes and the amount of methanotrophs between the species, V. vitis-idaea-rooted-soils indicating the strongest uptake. The effect of plant species and vegetation types on soil CH4 fluxes has also been shown by other studies (Praeg et al 2016;Maier et al 2017b). These differences can result from the different plant species effects on soil microbes, which may again result from the root exudates (Innes et al 2004).…”
Section: Discussionsupporting
confidence: 73%
“…The amounts of methanotrophs were mainly in line with the belowground fluxes: V. vitis-idaea soils had the most methanotrophs and the strongest average CH4 uptake, while the nonrooted soil had significantly less methanotrophs than the ericoid shrubs and seemed to be a small source of CH4. Praeg et al (2016) also reported increased CH4 uptake by forest soils with tree roots compared to nonrooted forest soil. The differences between the rooted and non-rooted soils are related to the presence of roots, which are in interdependent relationship with the soil microbes via the root exudates (Broeckling et al 2008).…”
Section: Discussionmentioning
confidence: 86%
“…The soil pH was measured using a glass electrode (PB-10, Sartorius, Göttingen, Germany). The glass electrode was set in a 1:2.5 soil-water solution at room temperature [38]. The available nitrogen (AN) content was determined by the alkaline hydrolysis diffusion method.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…For alpine soil arthropod abundance, experimental warming was most effective when combined with nutrient addition (Hågvar and Klanderud 2009), whereas a long-term warming experiment had no effect on richness and abundance of springtails in alpine subarctic ecosystems (Alatalo, Jägerbrand, and Čuchta 2015). Changes in occurrence and activities of microorganisms would be especially relevant to climate change considering their attributes as key players for methane formation and consumption, belonging to methanogenic archaea and methanotrophic bacteria, respectively (Crutzen and Lelieveld 2001;Hofmann et al 2016b;Praeg, Wagner, and Illmer 2017).…”
Section: Introductionmentioning
confidence: 99%